ChemInform Abstract: One‐Pot Cannizzaro Cascade Synthesis of ortho‐Fused Cycloocta‐2, 5‐dien‐1‐ones from 2‐Bromo(hetero)aryl Aldehydes. Issue 1 (17th December 2015) - Burroughs, Laurence; Eccleshare, Lee; Ritchie, John; Kulkarni, Omkar; Lygo, Barry; Woodward, Simon; Lewis, William
Abstract: Starting from 2‐bromo(hetero)aryl aldehydes, diverse terminal acetylenes and 1‐chloropropargyl(hetero)arenes an access to ortho‐fused cycloocta‐2, 5‐dien‐1‐ones is developed which tolerates various functional groups.